(untitled) (International Conference on Computers in Education, 2013)
This research aims to increase the ability of students to understand and improve their learning outcome when studying the subject of colligative solutions in chemistry. It also hopes to improve the ability of teachers to deliver the subject. This research was conducted at SMA Negeri IX Jakarta to the twelfth grade. It was a classroom action research carried out in five months comprising of two cycles. It involved two observers in the school. Based on the result, there is a significant increase of students’ test grades from cycle 1 to cycle 2, which is from 76.5 to 79.7. From the students’ learning effectiveness records, it is suggested that learning with interactive learning media can successfully improve students’ learning outcome, especially in the subject of colligative solution in Chemistry.